Pengaruh Penambahan Lantai Terhadap Kapasitas Struktur Eksisting Gedung Ruko yang Dialihfungsikan Menjadi Rumah Sakit - Silalahi, Oktavia Ully Artha (Syntax Corporation, 2026)
Hospital buildings play a strategic role in providing healthcare services and improving public health quality. The structure evaluated in this study is located on Jalan Iskandar Muda No. 278–280, Petisah Tengah, Medan, North Sumatra. Originally constructed as a commercial shop-house, the building was later converted into an eye hospital. The structural system adopts a Special Moment Resisting Frame (SMRF), determined based on site soil classification obtained from geotechnical investigation. Field data collection included structural dimensions, concrete strength, and reinforcement details. The evaluation focuses on beam and column elements, with columns acting as primary load-bearing components that directly resist additional loads from a planned one-story extension and roof structure. A three-dimensional structural model was developed using ETABS software, incorporating actual field data. Structural analysis was conducted under gravity and seismic loads using response spectrum analysis in accordance with SNI 1726:2019. Results indicate that the existing column structure is unable to withstand additional gravity loads and exhibits capacity ratios greater than one under seismic loading. Slab evaluation shows adequate flexural capacity (ϕMn = 11,452 kgm > Mu = 533.15 kgm). However, beam elements do not fully satisfy SMRF detailing requirements, although minimum span and width criteria are met. Column dimensions meet minimum geometric requirements but fail under capacity checks using spColumn analysis, with a ratio (ϕMn/Mu) of 0.50 at the second floor, indicating unsafe conditions. Furthermore, the strong column–weak beam principle is not satisfied, as beam moment capacity exceeds column capacity. Therefore, structural strengthening of columns is required before any vertical expansion is implemented.